Analysis of Determinants of Anemia Incidence in Third Trimester Pregnant Women - Sinambela, Megawati; Syahri, Alfi; Sitorus, Rotua Sumihar (Universitas Nahdlatul Ulama Surabaya, 2025)
Anemia in third-trimester pregnant women increases the risk of pregnancy complications such as preterm labor and low birth weight. Contributing factors include adherence to iron tablet consumption, maternal age, parity, nutritional status, and compliance with antenatal care (ANC) visits. This study aims to analyze the determinants of anemia in third-trimester pregnant women at the Gunung Selamat Labuhan Batu Health Center. This cross-sectional study involved 96 third-trimester pregnant women selected using consecutive sampling. Data were collected through interviews, hemoglobin level examinations, and evaluations of iron tablet adherence, nutritional status, and ANC visits. Data analysis used bivariate (chi-square) and multivariate (logistic regression) tests. Bivariate analysis showed a significant relationship between anemia and iron tablet adherence (p=0.00; PR=5.95), maternal age (p=0.00; PR=5.11), parity (p=0.00; PR=4.95), nutritional status (p=0.00; PR=7.55), and ANC visit compliance (p=0.00; PR=8.55). Multivariate analysis identified nutritional status (p=0.00; Exp(B)=16.69) and ANC visit compliance (p=0.00; Exp(B)=14.51) as the most dominant factors influencing anemia. Nutritional status and ANC visit compliance are key determinants of anemia in third-trimester pregnant women. Interventions focusing on nutritional education, ANC service optimization, and increased adherence to iron supplementation are essential to reduce anemia prevalence among pregnant women